2020
DOI: 10.1016/j.heliyon.2020.e04873
|View full text |Cite
|
Sign up to set email alerts
|

The effects of human platelet lysate versus commercial endothelial growth medium on the endothelial differentiation potential of human amniotic fluid mesenchymal stem cells

Abstract: To differentiate stem cells into endothelial cells, vascular endothelia growth factors (VEGF) serve as the major signal for stimulating the cells. However, there are other cytokines or growth factors associated with endothelial cell development and differentiation. Human platelet lysate (hPL) has been a promising reagent in cell-based therapy since it is considered as a source of bioactive molecules and growth factors. The aim of this study was to investigate the in vitro differentiation of human amniotic flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…In addition, others demonstrated that platelets or platelet-containing preparations can be used to promote the regenerative potential of human AD-MSC ( 30 ) and several studies have reported an improved therapeutic efficacy of MSC from different sources induced by platelet rich plasma ( 31 33 ). After numerous promising studies have reported the preservation of the basic characteristics of human BM- and AD-MSC with hPL ( 34 37 ), and functional studies using hPL ( 38 , 39 ) have also been carried out in human medicine, the time has come to perform functional assays for ePL as well.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, others demonstrated that platelets or platelet-containing preparations can be used to promote the regenerative potential of human AD-MSC ( 30 ) and several studies have reported an improved therapeutic efficacy of MSC from different sources induced by platelet rich plasma ( 31 33 ). After numerous promising studies have reported the preservation of the basic characteristics of human BM- and AD-MSC with hPL ( 34 37 ), and functional studies using hPL ( 38 , 39 ) have also been carried out in human medicine, the time has come to perform functional assays for ePL as well.…”
Section: Introductionmentioning
confidence: 99%